INCLUSIVISM AND EXCLUSIVISM AS WELL AS THEIR EFFECT ON ISLAMIC EDUCATION BASED MULTICULTURAL - Dhikrul Hakim (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2019)
Abstract. The majority of Indonesia's population embraces Islam, there are some of other religions and beliefs that are also recognized and adhered to by residents in this country, Christians, Catholics, Hindus, Buddhists and Confucians. Indonesian society is a society with a very complex level of diversity, the diversity is known as a multicultural society. This implies that without media in the form of education, plural theology will be difficult to develop in Indonesia. With education, we can have strong basics in understanding differences because essentially education is a process of "an effort to humanize humans". This method of scientific work uses qualitative methods with a library research approach. The results of this scientific work are, Religious education based multicultural that is a process of awareness based on tolerance which is intended as a comprehensive effort to prevent conflicts between religions, prevent religious radicalism, while at the same time foster the realization of positive appreciative attitudes towards plurality, inclusivism in dimensions and any perspective does not promote exclusivism. Religion should be able to be a promoter for humanity to always uphold the peace and improve the welfare of all human beings on this earth. Unfortunately, in real life, religion is often been one of the causes of humanity's violence and destruction. Thus, the fulcrum of religious education based multicultural inclusivism actually lies in the understanding and the effort to live together in the context of religious and cultural differences.